Propuesta para la implementación de luz solar como factor favorable energético en centros poblados del municipio de Mesitas del colegio (2023)
Mesitas del Colegio is considered to be a Municipality which has among its main benefits a good electrical energy service known as a small energy capital with little recognition, since it has three hydroelectric plants which are the Dario Valencia Hydroelectric Plant Samper – Emgesa, the La Guaca Hydroelectric Plant – EMGESA and the El Paraíso Hydroelectric Plant, it is important to recognize that Enel Emgesa makes use of seven hydroelectric plants, five with added value but within the two largest and most important being part of the hydroelectric chain Pagua are the Paraíso and the Guaca which are supplied by the muña reservoir, in this way it is important to recognize that the tourist festival and departmental reign of light is celebrated in the month of December, starting from here the idea of generating a photovoltaic solar energy system which is a favorable project with respect to the climatic conditions of the Municipality, based on the inclusion of the 3 capitals that it has, which are Pradilla, El Triunfo and La Victoria, all with important characteristics that make them stand out within Of the territory.